Influence of the presence of Al2O3 on Ni-Mo-W trimetallic catalysts for HDS. (18th August 2006) - Gochi-Ponce, Y.; Alvarez-Contreras, L.; Paraguay-Delgado, F.; Alonso-Nunez, G.
This work presents Ni-Mo-W tri-metallic catalysts of the type 'NEBULA', (Soled et al., 2001) bulk and supported, named NEBDMDS, NEB1 (5% Al2 O3 ), NEB2 (25% Al2 O3 ) and NEB3 (50% Al2 O3 ). The materials were prepared from water-soluble ammonium salts by direct precipitation with nickel nitrate. Supported catalysts were synthesised obtaining a gel, which was aged, dried and calcinated. The precursors were sulphiding in a tubular furnace with a flow of DMDS (Dimethyl-disulphide)/N2 . The generated catalysts were evaluated in the reaction of hydrodesulphurisation (HDS) of the dibenzothiophene (DBT). They were characterised by the adsorption of nitrogen using the Brunauer, Emmett and Teller (BET) method and Barrett Joyner and Halenda (BJH) method, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electronic Microscopy (TEM). The increase of the content of Al2 O3 in the catalysts influenced on the decrease of the catalytic activity. The NEBDMDS catalyst presented the catalytic activity higher of 13.1 mol/s g.